John M. answered • 04/22/14

Tutor

4.9
(551)
Analytical assistance -- Writing, Math, and more

Caleb, as I read this your second attempt 4x=(12)(6) gives x=18, but x≠OC, x=AC.

The secant formula is that the product of the full length of the secant from A to where it exits the Circle at B times the length of the secant from A to where it enters the circle at D is equal to the product of the full length of the secant from A to where it exits the circle at C times the length of the secant from A to where it enters the Circle at E. Or algebraically, (AB)(AD)=(AC)(AE), but we are given AE, AB and DB.

You need to use other geometry principles to calculate what you need. And we know that AD + DB = AB, and we know that AE + EC = AC. Finally, we know that EOC must be a diameter and OC a radius of the circle, so OC = 1/2 EC.

(12)(AD)=(AC)(4)

Since AD+DB=AB, AB-DB=AD, so 12-6=AD=6

(12)(6)=(AC)(4), so AC=18 [You did all the work up to this point]

AOC=AE+EOC, so 18=4 + EOC, so EOC = 14.

Since EOC is a diameter, OC is a radius and thus equal to half of EC or 7.